2007
DOI: 10.1016/j.jpowsour.2007.08.084
|View full text |Cite
|
Sign up to set email alerts
|

Microwave plasma chemical vapor deposition of nano-structured Sn/C composite thin-film anodes for Li-ion batteries

Abstract: In this paper we report results of a novel synthesis method of thin-film composite Sn/C anodes for lithium batteries. Thin layers of graphitic carbon decorated with uniformly distributed Sn nanoparticles were synthesized from a solid organic precursor Sn(IV) tert-butoxide by a one step microwave plasma chemical vapor deposition (MPCVD). The thin-film Sn/C electrodes were electrochemically tested in lithium half cells and produced a reversible capacity of 440 and 297 mAhg -1 at C/25 and 5C discharge rates, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 64 publications
(73 reference statements)
2
47
0
1
Order By: Relevance
“…4. Two intensive peaks of D-and G-band are allocated at Raman shifts of about 1,335 and 1,570 cm −1 , corresponding to A 1g and E 2g vibration modes of carbon atoms, respectively [26]. G band usually indicates the original feature of graphite, while D band suggests a disordered carbonaceous structure [27].…”
Section: Resultsmentioning
confidence: 99%
“…4. Two intensive peaks of D-and G-band are allocated at Raman shifts of about 1,335 and 1,570 cm −1 , corresponding to A 1g and E 2g vibration modes of carbon atoms, respectively [26]. G band usually indicates the original feature of graphite, while D band suggests a disordered carbonaceous structure [27].…”
Section: Resultsmentioning
confidence: 99%
“…An Sn-6.0 wt% C thin film had a high initial discharge capacity of 750 mAh g 1 ; however, more than 15% of the total capacity was lost after 10 dischargecharge cycles. In contrast, an Sn/C nanocomposite thin film prepared by microwave plasma chemical vapor deposition displayed much better anode performance [52]. TEM observation confirmed that this Sn/C thin film had a unique structure of thin layers of graphitic carbon decorated with uniformly distributed Sn nanoparticles, which produced reversible capacities of 423 and 297 mAh g 1 at C/25 (ca.17 mA g 1 ) and 5°C rates between 0 and 1.1 V, respectively.…”
Section: Sn-m (Active Element) Thin-film Anodesmentioning
confidence: 89%
“…Triethoxy(phenyl) silane was used as precursor. Details of the MPCVD method for nanostructured composite electrode manufacturing are described elsewhere [21]. Cycling voltage was set at the 0.05-1.4 V (half-cell containing Si-C) range.…”
Section: Methodsmentioning
confidence: 99%